On-nerve needle nerve conduction study in the sural nerve: A new technique for evaluation of peripheral neuropathy. Issue 9 (September 2015) - Oh, Shin J.; Hemmi, Shoji; Hatanaka, Yuki
Highlights Sensory compound nerve action potentials (CNAPs) were obtained by the on-nerve needle nerve conduction study (ONN-NCS) with needle electrodes placed on the exposed sural nerve during biopsy. The ONN-NCS showed higher amplitude and longer duration of the CNAP but a slower maximum nerve conduction velocity (NCV) than the SE-NCS and a significantly better concordance with the nerve biopsy. The ONN-NCS is a better electrophysiological test for the histopathological correlation with nerve biopsy.